English as a Lingua Franca in Portugal: What Students Want, What Teachers Teach - Guerra, Luís (2014)
This study seeks to show how Portuguese students and teachers view learning and using English today and how their attitudes can influence ELT policies and practices, not only in Portugal but in other European countries, in particular, and in the countries of the Expanding Circle, in general.